Faktor-faktor Yang Mempengaruhi Keputusan Wisatawan Menginap Di Villa Akasha Beach Estate Kerobokan Badung - Darma Harikusmawan, Gusti Bagus; Mandala, Kastawan (E-Jurnal Manajemen, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Which is the goal of this research is to ( 1 ) determine the factors that influence the tourist 's decision to stay at Villa Akasha Beach Estate Kerobokan Badung . ( 2 ) determine the variables that represent each of the factors that influence the decision of tourists staying at the villa , Akasha Beach Estate Kerobokan Badung . ( 3 ) determine the dominant factors that influence the decision of tourists staying at the villa , Akasha Beach Estate Kerobokan Badung . This study was performed in Akasha Beach Estate Villa Kerobokan Badung with factor analysis techniques . The number of samples obtained by using accidental sampling method was 120 respondents . Method of principal component analysis ( PCA ) , yielding six factors that affect the interest of tourists staying at Villa Akasha Beach Estate Kerobokan Badung . The six factors are social factors , dishes and education , products , services , promotions and environment . Variables representing each factor , namely : social factors represent the lifestyle , food and drink menu dish represents factors , the ability of employees represents a factor of products , fast service represents the service factor , representing the electronic media promotion factors and environmental factors represent the condition of the building . While the dominant influential factor is the environment . Suggestions that can be recommended is the management must pay attention to social factors rating , type of dish , product offerings, services , promotions are done , as well as Akasha Beach Estate villa neighborhood can influence decisions stay travelers . Keywords : tourist decision , the factors that influence it .